Mejoramiento poblacional del arroz irrigado con énfasis en el virus de la hoja blanca - Borrero Correa, Jaime C.; Châtel, M.; Triana Espinel, Mónica (Empresa Brasileira de Pesquisa Agropecuária, 2000)
The CIAT/CIRAD collaborative project aims to use recurrent selection to create and improve populations and gene pools containing the male-sterile gene and, from this, to develop improved lines and progenitors with traits needed by national programs. This study was to improve germplasm resistant to the "hoja blanca" (white leaf) virus and to fix this trait while preserving, at adequate levels, other traits of agronomic interest. Latin American national programs are expected to take advantage of this germplasm to develop other populations, progenitors, and/ or varieties. At present, after three cycles of selection and recombination, four populations are available with high levels of resistance to the virus, combined with other traits of agronomic interest. Furthermore, the project is responsible of registering, maintaining, and multiplying new populations and gene pools in Latin America, and for promoting the use of this germplasm among the region`s breeders. Exchange of seeds from these populations and gene pools, together with collaboration in preparing projects and forming populations, has been intense. Currently, the project is closely linked to projects developed in Argentina, Chile, Uruguay, and Venezuela.